DIAGNOSIS DAN PENATALAKSANAAN CEDERA SERVIKAL MEDULA SPINALIS - Maja, Junita P. S. (Jurnal Biomedik : JBM, 2013)
Abstract: Spinal cord injury is a traumatic lesion of the spinal cord which causes neurological disorders. The symptoms vary from pain, paralysis, and the occurence of incontinence, depending on the location of the injured spinal cord. The damage of the spinal cord may be incomplete or complete. We reported a 55-year-old male with his main complaint being weakness throughout all four limbs which occured after a fall with a hyperextended neck position. At the time of admission, the duration of injury was 12 hours. Physical examinations showed motoric and sensoric disorders, without any autonomic abnormalities. Cervical radiographics and a CT scan revealed no abnormalities, whereas the MRI images showed a contusion at C3. The management of this case included stabilization of the neck, a protocol treatment for cervical injuries, an administration of a high-dose of methylprednisolone, prevention of complications, and a regular session of physiotherapy. During treatment, the patient showed a significant progression in both motoric and sensoric functions. Conclusion: Based on all the tests performed and the follow-up, the diagnosis of this case was central cord syndrome (CCS) due to incomplete cervical medulla spinalis injury. Keywords: cervical injury, spinal cord, diagnosis, treatmentÂ Â  Abstrak: Trauma medula spinalis adalah trauma pada tulang belakang yang menyebabkan lesi di medula spinalis sehingga menimbulkan gangguan neurologik. Gejala-gejala dapat bervariasi mulai dari nyeri, paralisis sampai terjadinya inkontinensia, dan sangat bergantung pada lokasi medula spinalis yang mengalami cedera. Kerusakan medula spinalis dapat bersifat â€œinkomplitâ€ dan â€œkomplitâ€. Kami melaporkan kasus seorang laki-laki 55 tahun dengan kelemahan keempat anggota gerak yang terjadi setelah terjatuh dengan posisi leher yang hiperekstensi. Saat masuk rumah sakit, cedera sudah berlangsung selama 12 jam. Pada pemeriksaan fisik ditemukan gangguan motorik dan sensorik, sedangkan otonom tidak ditemukan kelainan. Gambaran radiologik foto servikal dan CT-Scan servikal tidak terdapat kelainan, sedangkan pada MRI tampak gambaran kontusio di segmen medula spinalis C3. Penanganan pada kasus ini yaitu stabilisasi leher, tatalaksana umum untuk cedera leher, pemberian metilprednisolon dosis tinggi, pencegahan komplikasi yang muncul, dan fisioterapi yang teratur. Selama perawatan pasien menunjukkan kemajuan yang berarti, baik dari fungsi motorik maupun sensorik. Simpulan: Berdasarkan hasil pemeriksaan yang telah dilakukan dan pemantauan lanjut selama perawatan, diagnosis yang ditegakkan ialah central cord syndrome (CCS) akibat cedera medula spinalis servikal inkomplit. Kata kunci: cedera servikal, medula spinalis, diagnosis, tatalaksana